Impedimetric Response of a Label-Free Genosensor Prepared on a 3-Mercaptopropionic Acid Capped Gallium Selenide NanocrystalModified Gold Electrode - Ndangili, Peter M.; Jijana, Abongile N.; Olowu, Rasaq A.; Mailu, Stephen N.; Ngece, Fanelwa R.; Williams, Avril; Waryo, Tesfaye T.; Baker, Priscilla G.L.; Iwuoha, Emmanuel I. (My University, 2011)
Biocompatible and water soluble 3-mercaptopropionic acid cappedgallium selenide nanocrystals were synthesized from hydrated gallium (III) perchlorate and selenide ions. The nanocrystals were non-fluorescent but showed a sharp UV-vis absorption maximum at 260 nm.Transmission electron micrographs showed the formation of high quality non-aggregated particles with an average diameter of 65 nm. Gold electrode modified with the capped nanocrystals was used as a platform for impedimetric genosensing using NH2-5′-CCCACCGGTCCTTCATGTTC-3′ (probe) and 5′-GAACATGAAGGA CCGGTGGG-3′ (target) oligonucleotide sequences. The target oliginucleotide sequence is a component of5-enolpyruvylshikimate-3-phosphate synthase, a common vector gene in glyphosate resistant transgenic plants. The impedimetric genosensor exhibited high sensitivity towards the target DNA (sensitivity = 11.61 Ω/nM) with a detection limit of 0.66 nM (3s, n = 8). The genosensor was able to discriminate between complementary, non-complementary and 3-base mismatched target sequences and maintained 87 % of its response towards the target DNA after one month.
Keywords: Gallium selenide; Impedimetric genosensor; transmission electron microscopy (TEM); Electrochemical impedance spectroscopy (EIS); 5-enolpyruvylshikimate-3-phosphate synthase (CP4 espsp)